Leaf surfaces and neolithization - the case of Arundo donax L - Nunes, Sílvia C.; Gomes, Ana P.; Nunes, Paulo; Fernandes, Mariana; Maia, Ana; Bacelar, Eunice; Rocha, João; Cruz, Rebeca; Boatto, Aline; Ravishankar, Ajith P.; Casal, Susana; Anand, Srinivasan; et al. (Frontiers in Plant Science, 2022)
Arundo donax L. (Arundinoideae subfamily, Poaceae family) is a sub-tropical and temperate climate reed that grows in arid and semi-arid environmental conditions, from eastern China to the Mediterranean basin, suggesting potential adaptations at the epicuticular level. A thorough physical-chemical examination of the adaxial and abaxial surfaces of A. donax leaf was performed herein in an attempt to track such chemophenetic adaptations. This sort of approach is of the utmost importance for the current debate about the hypothetical invasiveness of this species in the Mediterranean basin versus its natural colonization along the Plio-Pleistocene period. We concluded that the leaf surfaces contain, apart from stomata, prickles, and long, thin trichomes, and silicon-rich tetralobate phytolits. Chemically, the dominating elements in the leaf ashes are oxygen and potassium; minor amounts of calcium, silicon, magnesium, phosphorous, sulphur, and chlorine were also detected. In both surfaces the epicuticular waxes (whose density is higher in the adaxial surface than in the abaxial surface) form randomly orientated platelets, with irregular shape and variable size, and aggregated rodlets with variable diameter around the stomata. In the case of green mature leaves, the dominating organic compounds of the epicuticular waxes of both surfaces are triterpenoids. Both surfaces feature identical hydrophobic behaviour, and exhibit the same total transmittance, total reflectance, and absorption of incident light. The above findings suggest easy growth of the plant, remarkable epidermic robustness of the leaf, and control of water loss. These chemophenetic characteristics and human influence support a neolithization process of this species along the Mediterranean basin.